English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

This equation is quadratic in form, that is, it can be transformed into a quadratic equation by a change in variables, and solved by the usual methods of solving quadratics.
replace y = x^2, so that x = +/- sqrt y.
Then solve
y^2 - 5y + 6 = 0..
factor and solve by the zero factor theorem
(y-3)(y-2) = 0
y = 3 or y = 2
x = +/- sqrt 3 or +/- sqrt 2
For more info see..
http://www.wtamu.edu/academic/anns/mps/math/mathlab/col_algebra/col_alg_tut20_quadform.htm
http://www.purplemath.com/modules/solvquad.htm

2007-02-06 14:44:03 · answer #1 · answered by Joni DaNerd 6 · 4 0

x^4 - 5x^2 + 6 = 0
(X^2 - 2)(X^2 - 3) = 0
(X^2 - 2) = 0 (X^2 - 3) = 0
X^2 = 2 X^2 = 3
X =+- SQRT(2) X = +-SQRT(3)

2007-02-06 14:45:34 · answer #2 · answered by MATHMANRET 2 · 4 0

(x^2-2)(x^2-3)=0
x^2-2=0
x^2-3=0
x=±√2 and ±√3

2007-02-06 15:20:51 · answer #3 · answered by Anonymous · 3 0

(x^2-2)(x^2-3)

(x+1)(x-2)(x+1)(x-3)

x=(-1)
x=2
x=(-1)
x=3

2007-02-06 14:56:38 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers